2019
DOI: 10.3390/polym11101570
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Formation and Stabilization by Biomolecules: The Leading Role of Cellulose

Abstract: Emulsion stabilization by native cellulose has been mainly hampered because of its insolubility in water. Chemical modification is normally needed to obtain water-soluble cellulose derivatives. These modified celluloses have been widely used for a range of applications by the food, cosmetic, pharmaceutic, paint and construction industries. In most cases, the modified celluloses are used as rheology modifiers (thickeners) or as emulsifying agents. In the last decade, the structural features of cellulose have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 97 publications
2
88
0
Order By: Relevance
“…Oil-in-water nanoemulsions (O/W) exhibit a great ability to carry large quantities of hydrophobic substances in the dispersed phase and protect them from degradation. Such emulsions consist of oil droplets coated by thin polymer shells and suspended in an aqueous medium [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], so they can also be treated as dispersions of nanocapsules. They may serve as carriers of corrosion inhibitors, pesticides, and antimicrobial agents [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oil-in-water nanoemulsions (O/W) exhibit a great ability to carry large quantities of hydrophobic substances in the dispersed phase and protect them from degradation. Such emulsions consist of oil droplets coated by thin polymer shells and suspended in an aqueous medium [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], so they can also be treated as dispersions of nanocapsules. They may serve as carriers of corrosion inhibitors, pesticides, and antimicrobial agents [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particles with high aspect ratio, such as rod-shaped cellulose nanomaterials and other polysaccharides, are advantageous for Pickering emulsion stabilization, since they require lower concentration compared to spherical particles [ 83 ]. The behavior of polysaccharide nanomaterials at the interphase has been subject of recent reviews [ 67 , 84 , 85 ]. Oza and Frank reported the earlier scientific studies that demonstrated the ability of microcrystalline cellulose to stabilize oil-in-water ( o / w ) and multiple ( w / o / w ) emulsions.…”
Section: Methods Of Microcapsule Fabricationmentioning
confidence: 99%
“…Use of these sources of cellulose to stabilize PEs does not compete with agricultural resources used for human consumption and can bring economical value from co-products [ 22 , 23 ]. All these advantages explain the important increase of research on PEs stabilized with cellulose, and some review articles have already been published [ 2 , 24 , 25 ] to show that cellulose microcrystals and microfibrils can stabilize PEs. Cellulose NanoCrystals (CNCs) and NanoFibrils (CNFs) demonstrated a better potential to stabilize PEs but nanocellulose production is relatively complex.…”
Section: Introductionmentioning
confidence: 99%